2022
DOI: 10.1007/s00380-022-02184-y
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction of the frailty syndrome in patients with severe mitral regurgitation

Abstract: In this prospective observational study, we investigated the impact of geriatric syndromes and frailty on mortality and evaluated the prognostic value of different frailty, nutritional, and geriatric assessment tools in high-risk patients with severe mitral valve regurgitation (MR) who were evaluated for mitral valve therapies including surgical, interventional, and conservative treatment options. We prospectively assessed multiple parameters including the CONUT Score, the Katz Index of independence in activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recently, Shamekhi et al . evaluated different frailty assessment tools in 127 patients suffering from severe symptomatic MR and who required surgical/interventional treatment or received conservative monitoring 27 . They found that geriatric syndromes and frailty were associated with an increased mortality in high‐risk patients with symptomatic severe MR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shamekhi et al . evaluated different frailty assessment tools in 127 patients suffering from severe symptomatic MR and who required surgical/interventional treatment or received conservative monitoring 27 . They found that geriatric syndromes and frailty were associated with an increased mortality in high‐risk patients with symptomatic severe MR.…”
Section: Discussionmentioning
confidence: 99%